Modern Missionaries: Canadian Postwar Technical Assistance Advisors in Southeast Asia - Webster, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
Postwar Canadian approaches to Asia were often in the non-governmental realm, drawing on the country’s missionary heritage. While diplomats in Ottawa worked for pro-Western states in the political realm, Canadian policies on economic development also aimed at building new states in the Canadian image. Canadians in government, transnational and non-governmental positions offered their own country as a modelThe international experts called together by the UN Technical Assistance Administration were central to Canadian postwar hopes and aspirations. The Administration, headed by Canadian civil servant Hugh Keenleyside, also included staff member George Cadbury, previously director of the Saskatchewan CCF government’s Economic Planning Board. It was individual Canadian technical advisers like these who offered the hands-on advice and played the crucial role in shaping policy taken by Southeast Asian states. These “modern missionaries” imagined themselves as part of a transnational community, one in which Canada could play a leadership role by being an active member of multilateral organizations.This paper examines the experience and role of postwar Canadian technical advisers in Southeast Asia, drawing on selected cases from the 1950s and 1960s. After considering the influence of the Canadian Cooperative Commonwealth Federation (CCF) on the idea of planning, it looks at F.R. Scott, the Montreal law professor and poet who served as the first UN Technical Assistance Resident Representative in Burma; Benjamin Higgins, the McGill economist who served as first financial advisor for the Indonesian National Planning Bureau; and J.T. Cawley, the Saskatchewan deputy minister of natural resources who was chief petroleum advisor to the Indonesian government.